2014
DOI: 10.4103/1658-354x.130677
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the effect of caudal dexmedetomidine versus morphine added to bupivacaine in pediatric infra-umbilical surgery

Abstract: Background:One of the most commonly used regional anesthetic techniques in pediatric surgeries is the caudal epidural block. Its main disadvantage remains the short duration of action. Hence, different additives have been used. Dexmedetomidine is a potent as well as highly selective α2 adrenergic receptor agonist. The aim of this randomized, double-blinded, study was to compare the duration of postoperative analgesia of caudal dexmedetomidine versus morphine in combination with bupivacaine in pediatric patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 19 publications
(21 reference statements)
2
18
0
Order By: Relevance
“…The assessment of postoperative pain was done hourly in the recovery room and in surgical ward with the help of Numeric Rating Scale (110) (4). Zero was considered as no pain, 1–3 as mild pain, 4–6 as moderate pain and 7–10 as severe pain.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of postoperative pain was done hourly in the recovery room and in surgical ward with the help of Numeric Rating Scale (110) (4). Zero was considered as no pain, 1–3 as mild pain, 4–6 as moderate pain and 7–10 as severe pain.…”
Section: Methodsmentioning
confidence: 99%
“…Various clinical trials performed in both animals and humans have shown dexmedetomidine to be safe when used as an adjuvant to local anesthetic in subarachnoid, caudal, epidural, and BPBs. [ 3 4 5 ] Dexmedetomidine has been used in a dose ranging from 30 to 100 μg in human BPBs. [ 5 6 ] There have been contradictory reports regarding the safety of dexmedetomidine on increasing its dose.…”
Section: Introductionmentioning
confidence: 99%
“…Morphine was one of the first additives used in 1981. Since then, many studies have been reported on its efficacy, its inhibitory effects, and on alternatives to the use of morphine . At our institution, pain management for infants undergoing upper abdominal surgery has evolved over time, transitioning from caudal morphine to PVC.…”
Section: Discussionmentioning
confidence: 99%